THE EFFECTIVENESS OF MANAGEMENT OF SOCIAL PROBLEMS OF BEGGERS, VARIETIES, AND INDEPENDENT PERSONS IN CENTRAL JAVA SOCIAL SERVICES - Lalu Satria Utama,; Ridwan Ainun Firdaus,; Syaefullah, Syaefullah (International Journal of Social Science, 2023)
The Unemployment, Homeless, and Abandoned Persons (PGOT) in Central Java Province in the period 2020-2021 has decreased but what happened at the PGOT Social Service Orphanage Mardi Utomo repeated that PGOT had received training back into the orphanage because they could not be independent. The purpose of this study was to determine the effectiveness of PGOT management in Central Java through the Social Service of Central Java Province. This study used a qualitative descriptive research method through direct interviews with ASN in the Social Service and Mardi Utomo PGOT Social Service Institutions. The results of the research, social rehabilitation efforts at the Mardi Utomo Home are still not maximized, as a result beggars, homeless people and abandoned people in Central Java Province even return to the streets & decide to return to the orphanage so that their lives are guaranteed by the state when coaching in the orphanage